2010
DOI: 10.1016/j.jasms.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectra of C6H+ and C6H3+ in the gas phase

Abstract: Measurement of the 3 ⌸ Ϫ 3 ⌸ transition of C 6 H ϩ in the gas phase near 19486 cm Ϫ1 is reported. The experiment was carried out with a supersonic slit-jet expansion discharge using cavity ringdown absorption spectroscopy. Partly resolved P lines and observation of band heads permitted a rotational contour fit. Spectroscopic constants in the ground and excited-state were determined. The density of ions being sampled is merely 2 ϫ 10 8 cm Ϫ3 . Broadening of the spectral lines indicates the excited-state lifetim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…12, indicated by #, was also observed in the aforementioned studies. 21,35 This again demonstrates that these features of decreased absorption are not just artifact features. Bands XIII and XIV: B 2 Π Ω ´X2 Π Ω vibronic band In the frequency range 19 587 ´19 600 cm ´1 another composite band feature has been observed which again is heavily overlaid by sharp C 2 (0,0) and (1,1) Swan band transitions.…”
Section: B a N D X C 6 H : B A N D I Xmentioning
confidence: 71%
See 4 more Smart Citations
“…12, indicated by #, was also observed in the aforementioned studies. 21,35 This again demonstrates that these features of decreased absorption are not just artifact features. Bands XIII and XIV: B 2 Π Ω ´X2 Π Ω vibronic band In the frequency range 19 587 ´19 600 cm ´1 another composite band feature has been observed which again is heavily overlaid by sharp C 2 (0,0) and (1,1) Swan band transitions.…”
Section: B a N D X C 6 H : B A N D I Xmentioning
confidence: 71%
“…Figure shows a recording of a band centered at 19 486 cm –1 . In a previous study this band feature was associated to the 2 A″–X 2 A″ electronic transition of the C 4 H 4 + cation, whereas in another study, it was identified as a 3 Σ – –X 3 Σ – transition of the C 6 H + cation . Because the spectrum is overlaid by a number of strong and sharp C 2 Swan transitions, particularly in the region where a Q branch of a possible 2 Π 3/2 – 2 Π 3/2 transition of C 6 H may be expected, an unambiguous assignment of this band is difficult.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations